Artemisinin Alleviates Cerebral Ischemia/Reperfusion-Induced Oxidative Damage via Regulating PHB2-Mediated Autophagy in the Human Neuroblastoma SH-SY5Y Cell Line. (15th December 2022) - Jiang, Menghan; Lai, Xiaoyi; Zhang, Yongjiang; Shen, Mengmeng; Ma, Hongxia; Liu, Anran; Wu, Jiannan; Yan, Junqiang
Abstract : Oxidative stress plays a key role in cerebral ischemia/reperfusion injury. Artemisinin (ART) has antioxidative stress activity in addition to its powerful antimalarial effects. In this article, we investigated the effect of ART on OGD/R-induced oxidative stress injury and its underlying mechanisms. We used oxygen-glucose deprivation/reoxygenation (OGD/R) to establish an in vitro model of cerebral ischemia/reperfusion (I/R) injury. CCK-8 and lactate dehydrogenase (LDH) release were used to assess cellular damage. Measurement of reactive oxygen species (ROS), malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), and mitochondrial membrane potential (MMP) estimates oxidative stress-induced damage and protection from ART effect. OGD/R treatment aggravated oxidative stress damage, whereas ART reversed the effects of OGD/R. Autophagy is closely related to oxidative stress; in order to confirm whether the antioxidative stress effect of ART is related to PHB2-mediated autophagy, we examined the protein expression of prohibitin 2 (PHB2), TOMM20, p62, and the conversion of microtubule-associated protein light chain 3I (LC3I) to LC3II and found that the protein expression of PHB2, TOMM20, p62, and LC3II/LC3I was significantly correlated with OGD/R treatment. The colocalization of PHB2 and LC3, TOMM20, and LC3 was reduced after OGD/R treatment, and ART reversed this change. After silencing PHB2, the protective effect of ART against OGD/R-induced oxidative stress injury was reduced, the protein expressions of PHB2, TOMM20 and LC3II/LC3I and the colocalization of PHB2 and LC3, TOMM20, and LC3 were decreased. We used chloroquine to block the lysosomal pathway and found that ART increased the conversion of LC3I to LC3II, silencing PHB2 which inhibited the conversion of LC3I to LC3II, and impaired mitophagy. Our findings showed that ART attenuated OGD/R-induced oxidative stress damage through PHB2-mediated mitophagy. To the current knowledge, our study is the first to demonstrate that ART attenuates OGD/R-induced oxidative stress injury through PHB2-mediated autophagy in the human neuroblastoma SH-SY5Y cell line, which provided new insights into the treatment of OGD/R injury.